2016
DOI: 10.1371/journal.pgen.1006397
|View full text |Cite
|
Sign up to set email alerts
|

The Sweet Potato NAC-Domain Transcription Factor IbNAC1 Is Dynamically Coordinated by the Activator IbbHLH3 and the Repressor IbbHLH4 to Reprogram the Defense Mechanism against Wounding

Abstract: IbNAC1 is known to activate the defense system by reprogramming a genetic network against herbivory in sweet potato. This regulatory activity elevates plant defense potential but relatively weakens plants by IbNAC1-mediated JA response. The mechanism controlling IbNAC1 expression to balance plant vitality and survival remains unclear. In this study, a wound-responsive G-box cis-element in the IbNAC1 promoter from -1484 to -1479 bp was identified. From a screen of wound-activated transcriptomic data, one transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…For example, in Arabidopsis, a positive regulator, Enhanced Em level (EEL) and a negative regulator, ABA‐INSENSITIVE 5 (ABI5), regulate expression of one of the late embryogenesis‐abundant ( LEA ) genes, AtEm1 , through a competitive binding to the same cis ‐element (Bensmihen et al ., ). In sweet potato, TFs competitive binding to the same cis ‐element is involved in plant defence against herbivory (Chen et al ., ). In response to wounding, the IbbHLH3 homodimer activates the defence network through direct binding and activation of IbNAC1 gene expression.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, in Arabidopsis, a positive regulator, Enhanced Em level (EEL) and a negative regulator, ABA‐INSENSITIVE 5 (ABI5), regulate expression of one of the late embryogenesis‐abundant ( LEA ) genes, AtEm1 , through a competitive binding to the same cis ‐element (Bensmihen et al ., ). In sweet potato, TFs competitive binding to the same cis ‐element is involved in plant defence against herbivory (Chen et al ., ). In response to wounding, the IbbHLH3 homodimer activates the defence network through direct binding and activation of IbNAC1 gene expression.…”
Section: Discussionmentioning
confidence: 97%
“…In response to wounding, the IbbHLH3 homodimer activates the defence network through direct binding and activation of IbNAC1 gene expression. To terminate the response, IbbHLH3–IbbHLH4 heterodimer, which downregulates IbNAC1 expression, competes with the IbbHLH3 homodimer for binding to the same cis ‐element within IbNAC1 promoter (Chen et al ., ). ZmbHLH80 and ZmbHLH90 may function in a similar way.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have shown that NAC proteins are widely involved in various signaling pathways [ 10 , 11 ], growth and development [ 5 , 12 , 13 ] and senescence [ 11 , 14 , 15 ], in response to hormones [ 11 , 16 ] and biotic [ 17 , 18 , 19 , 20 ] and abiotic stress [ 21 , 22 , 23 ]. For instance, NAM gene from petunia determines the positions of meristems [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sweet potato is one of the most important food crops with high resistance to stress, especially wounding. Several researchers indicated that multiple transcriptional regulations are activated against wounding in sweet potato (Lin et al, 2012, 2013, 2014; Chen et al , 2016a, b; Li et al , 2016). In this study, we further investigate the wound-repressible miRNAs in sweet potato.…”
Section: Introductionmentioning
confidence: 99%